ANALYSIS OF CONSUMER DECISIONS IN PURCHASING SMARTPHONES BASED ON PRODUCT QUALITY, PROMOTION AND PRODUCT DESIGN Shandrya Victor Kamanda - Shandrya Victor Kamanda (LPPM Universitas Ibnu Sina, 2024)
The need for technology today leads consumers to access the internet in almost every activity. This makes consumers must have a smartphone as a support in accessing the internet. With the many alternative smartphone brands offered, it can support consumer decision making through considerations taken based on the offerings of each brand. This study aims to analyse promotion, product design and product quality on smartphone purchasing decisions at SP Plaza and its surroundings. This study concludes that quality affects consumer decisions in buying smartphones, while product design and promotion do not affect consumer decisions in buying smartphones. Similar designs are owned by various smartphone brands and both carry out promotions, so consumers will certainly focus on the quality of the smartphone.